INNOVATOR SOCIAL MEDIA AND THE EMERGENCE OF A TOURISM DESTINATION - Jaya, Pajar Hatma Indra (Jurnal Sosial Humaniora, 2024)
Many regions in Indonesia have tourism assets that take work to develop into new tourist destinations. Seeking any pattern in developing a new tourism destination applicable to Indonesia with excellent tourism potential, this study becomes essential. It analyses how Gili Ketapang, a village in Probolinggo, East Java, became a new tourism destination. The researchers used a qualitative descriptive-analytical method. The data collection applies observation, documentation, and interviews with twelve informants involved in a snowball method. The primary analysis is an interactive analytical model. This research found that Gili Ketapang’s growth into a tourism destination started with an initiative from an innovator aware of the tourist assets. The innovator had the confidence and courage to package and offer the tourism assets via social media. Once the business was successful, it encouraged other local people to get involved, and eventually, the region became a new tourist destination. Creating a tourist destination does not require big investors but an innovator. This research provides recommendations for building a tourist destination to portray their tourism assets vividly, build big dreams, design tourism packages, and broadcast them to the public through effective media communications.